Fine Spectra of Symmetric Toeplitz Operators - Muhammed Altun (Abstract and Applied Analysis)
The fine spectra of 2-banded and 3-banded infinite Toeplitz matrices were examined by several authors. The fine spectra of n-banded triangular Toeplitz matrices and tridiagonal symmetric matrices were computed in the following papers: Altun, “On the fine spectra of triangular toeplitz operators” (2011) and Altun, “Fine spectra of tridiagonal symmetric matrices” (2011). Here, we generalize those results to the (2𝑛+1)-banded symmetric Toeplitz matrix operators for arbitrary positive integer 𝑛.